Adoption of pleurectomy and decortication for malignant mesothelioma leads to similar survival as extrapleural pneumonectomy - YILDIZELİ, BEDRETTİN; BATIREL, HASAN FEVZİ; YUMUK, PERRAN FULDEN (MOSBY-ELSEVIER, 2016)
Objective: We changed our surgical approach to malignant pleural mesothelioma (MPM) in August 2011 and adopted pleurectomy and decortication (PD) instead of extrapleural pneumonectomy (EPP). In this study, we analyzed our perioperative and survival results during the 2 periods. Methods: All patients who underwent surgical intervention for MPM during 2003-2014 were included. Data were retrospectively analyzed from a prospective database. Before August 2011, patients underwent evaluation for EPP and adjuvant chemoradiation (group 1). After August 2011, patients were evaluated for PD and adjuvant chemotherapy and/or radiation (group 2). Demographic characteristics, surgical technique, histology, side, completeness of resection, and types of treatments were recorded. Statistics was performed using Student t test, chi(2) tests, uni- and multivariate regression, and Kaplan-Meier survival analysis. Results: The same surgical team operated on 130 patients. Median age was 55.7 years (range, 26-80 years) and 76 were men. EPP and extended PD was performed in 72 patients. Ninety-day mortality was 10%. Median survival was 17.8 months with a 5-year survival rate of 14%. Uni- and multivariate analyses showed that epithelioid histology, stage N0, and trimodality treatment were associated with better survival (P=.039, P=.012, and P<.001, respectively). Demographic variables and overall survival (15.6 vs 19.6 months, respectively) were similar between the groups, whereas nonepithelioid histology, use of preoperative chemotherapy, and incomplete resections were more frequent in group 2 (P<.001, P<.001, and P=.006, respectively). Follow-up was shorter in group 2 (22.5 +/- 20.6 vs 16.4 +/- 10.9 months; P<.001). Conclusions: Adoption of PD as the main surgical approach is not associated with survival disadvantage in the surgical treatment of MPM.
Keywords: malignant pleural mesothelioma; extrapleural pneumonectomy; pleurectomy; decortication; LONG-TERM SURVIVAL; PLEURAL MESOTHELIOMA; INTERNATIONAL MESOTHELIOMA; TRIMODALITY THERAPY; RADICAL PLEURECTOMY; SURGERY; PLEURECTOMY/DECORTICATION; CHEMOTHERAPY; MANAGEMENT; MARS